Contaminants in Agriculture and Environment: Health Risks and Remediation 2019
DOI: 10.26832/aesa-2019-cae-0157-06
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment and mitigation of heavy metal pollution in agriculture and environment

Abstract: Heavy metals contamination in agricultural environment and its deleterious effects on the crops and human health is an issue of serious concern in the present time. Agricultural fields receive various heavy metals such as Zn, Ni, Mn, Cu, Cd, Cr, Pb, As and Hg etc. mainly from natural and anthropogenic sources. The greater concentration of heavy metals in the fields spoils the soil characteristics and has extreme consequences on both crops and human. Their persistence and non-degradable nature increases its acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Tetraethyl lead was used as a gasoline additive to increase the octane rating, before the EPA banned its use in gasoline in 1996 in the USA. Leaded gasoline is still used for propeller planes and some race cars [1,19]. Metallic lead is a bluish, gray-silver soft metal.…”
Section: Lead and Lead Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetraethyl lead was used as a gasoline additive to increase the octane rating, before the EPA banned its use in gasoline in 1996 in the USA. Leaded gasoline is still used for propeller planes and some race cars [1,19]. Metallic lead is a bluish, gray-silver soft metal.…”
Section: Lead and Lead Compoundsmentioning
confidence: 99%
“…It is mostly performed on-site and is widely accepted. Microorganisms and plants use different mechanisms for bioremediation of contaminated water and soils [44,45,46]. The bioremediation process occurs through a variety of mechanisms like redox, adsorption, complexation, ion exchange, precipitation and electrostatic attraction [47].…”
Section: Mitigation Of Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outros, contudo, como o cádmio, não apresentam função biológica conhecida, causando sérios problemas devido a sua toxicidade, aliada aos fenômenos de bioacumulação (Dal'corso, 2012;Furini, 2012). A contaminação dos solos agrícolas por metais pesados é uma séria preocupação na atualidade, uma vez que estes são persistentes no solo e facilmente absorvidos e acumulados pelas plantas (Kumar et al, 2019a). O cádmio é introduzido nos solos indiretamente (deposição atmosférica) através de práticas antropogênicas como a mineração, queima de lixo e de combustíveis fósseis.…”
Section: Introductionunclassified
“…In particular, soils in the floodplains can store matter, such as carbon, salts, or metals [1,2]. Since many floodplains are used for food production [3,4], metal contamination of soils can be detrimental to human health [5,6]. Studies on metals such as cadmium (Cd), chromium (Cr), nickel (Ni), lead (Pb) and zinc (Zn) have shown that they affect soil biota and can accumulate in plants growing in the soils, potentially entering the human food chain [7][8][9].…”
Section: Introductionmentioning
confidence: 99%